Peran Regulasi dalam Mendorong Adopsi Cloud Computing UMKM DKI Jakarta - Muhammad Rizal; Ruslaini Ruslaini; Eri Kusnanto (Journal Of Business, Finance, and Economics (JBFE), 2022)
This study aims to understand SMEs' perspectives on the impact of regulation on their decisions to adopt cloud computing technology. The research employs a qualitative method with a phenomenological approach to explore the experiences of SME owners, managers, and IT professionals regarding regulatory frameworks affecting cloud computing adoption decisions. Data were collected through interviews with SMEs in the DKI Jakarta region and analyzed using thematic analysis. The findings indicate that government regulations play a crucial role in shaping cloud adoption strategies among SMEs. However, ambiguous and complex regulations present challenges and hinder SMEs' efforts to adopt cloud computing. Despite these obstacles, SMEs demonstrate resilience and flexibility in navigating regulatory challenges by utilizing certified and recognized cloud service providers, thereby mitigating risks associated with regulatory compliance. This study provides insights for policymakers and practitioners to support cloud computing adoption in the SME sector, helping them maintain competitiveness in increasingly competitive markets.